Jalur Saraf Vergence : Systematic Literature Review - Zalafi Kartika Azka; Alvian Dwisakti Kurniato (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Vergence movement is an important mechanism in eye coordination to maintain visual focus. The neural pathways controlling vergence involve complex interactions between various brain structures, such as the mesencephalic nucleus of the oculomotor nerve (CN III), the abducens nucleus (CN VI), the reticular pontine formation (PRF), and the visual and motor cortices. Disorders in this system can lead to convergence insufficiency, esotropia, exotropia, as well as diplopia which impacts the quality of binocular vision. This study aims to conduct a systematic review of the neural pathways that play a role in the vergence system. This research design is a study that uses the Systematic Literature Review (SLR) method. 5 articles were obtained using a method of secondary analysis of literature review through scientific database portals such as SINTA, Scopus and Google Scholar published in 2015-2025 both national and international articles. The results of the analysis show that vergence disorders are common in children and the elderly, with various causes ranging from benign factors to more serious neurological conditions. Studies show that activities in the parietal eye field (PEF), frontal eye field (FEF), superior colliculus (SC), and PRF have important roles in vergence coordination. In addition, vergence deficits were also found in Parkinson's patients, who showed prolonged latency and reduced vergence gain. In the context of technology, research on virtual reality (VR) shows that vergence errors often occur when users interact with virtual environments, leading to visual fatigue and incorrect depth perception. This study also highlights that neurotransmitters such as GABA, glutamate, and dopamine have a role in the modulation of neural signals that control vergence. A deeper understanding of the neural pathways of vergence is crucial in ophthalmology and neurology, especially in the diagnosis and therapy of binocular vision disorders. In addition, research on vergence also contributes to the development of visual technologies, such as VR and eye tracking systems, that are more adaptive to human physiological characteristics.